ERP evidence for memory and predictive mechanisms in word-to-text integration - Stafura, Joseph Z. (Lang Cogn Neurosci, 2015)
During reading, word-to-text integration processes proceed quickly and incrementally through both prospective (predictive) and retrospective (memory) processes. Across a sentence boundary, where prediction may be less functional, memorial processes may be especially important. We tested predictive and memory mechanisms with event-related potentials (ERPs) recorded on the first content word across a sentence boundary by manipulating the direction of association between this word and one from the preceding sentence. For comparison with this text comprehension (TC) task, we tested these same word pairs in a word meaning judgment (MJ) task. In both tasks we found reduced N400 amplitudes over central scalp electrodes when the two words were either forward-associated (FA) or backward-associated (BA), relative to task-specific baseline conditions. In the MJ task, FA pairs produced a greater reduction in the N400 reduction than BA pairs over right parietal areas. However, in the TC task, BA pairs produced a greater N400 reduction than FA pairs over left parietal electrodes. A temporal principal component analysis of TC and MJ data showed a component reflecting the central N400. Additional components from TC data reflected FA-BA differences during early (N200) and late (parietal N400 and LPC) phases of processing. Comprehension skill predicted association effects in the MJ task, especially FA, and the BA central N400 effects in the TC task. The results demonstrate that, beyond N400 indicators of prediction effects, ERPs reflect the role of memory processes in word-to-text integration across sentences, part of a dynamic interplay between anticipatory and memorial processes that support comprehension.